SPAD-502 and atLEAF CHL PLUS values provide good estimation of the chlorophyll content for Hevea brasiliensis Müll. Arg. Leaves - Andi Nur CAHYO; Rudi Hari MURTI; Eka Tarwaca Susila PUTRA; Tri Rini NURINGTYAS; Denis FABRE; Pascal MONTORO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2020)
Measurement of chlorophyll content using destructive methods is not efficient due to a large number of samples, cost, and time needed. Estimationof chlorophyll content by nondestructive methods using handheld chlorophyll meter may be considered to improve efficiency. This research aimed to determine the formula to convert SPAD-502 and atLEAF CHL PLUS values (relative indicator of chlorophyll content) to estimated (absolute) rubber leaves chlorophyll content. Twenty leaves of rubber plant were measured using SPAD-502 and atLEAF CHL PLUS at the same time to determine SPAD-502 and atLEAF CHL PLUS values. The measured leaves were then collected to determine the chlorophyll content using a standard laboratory procedure. Regression and correlation analyses (among 3 methods) were conducted using SAS v.9 software. The results showed that between SPAD-502 and atLEAF CHL PLUS values were closely correlated, hence both of the devices can substitute each other to estimate rubber leaf chlorophyll content. In addition, the relationship between atLEAF CHL PLUS and SPAD-502 values with actual chlorophyll content of rubber clone SP 217, PB 260, GT1, and all clones (general) were significant with high coefficient of determination (R2) as well as low Root Mean Square Error (RMSE) and Coefficient of Variation (CV). Therefore, by using formula determined in this study, both atLEAF CHL PLUS and SPAD-502 can be suggested for accurate, fast, and non-destructive estimation of chlorophyll content of rubber plant leaf.